Climate-Induced Spatio-Temporal Shifts in Natural and Agro-ecosystems in the Middle East and North Africa Region : A Synthesis Report - World Bank (World Bank, Washington, DC, 2021)
Recent assessments by the Intergovernmental Panel on Climate Change (IPCC) indicate that many regions of the world will experience biome-level changes, suggesting that areas that presently feature deserts, rainforest, or tundra may no longer have the same type of vegetation by the end of this century. As biomes shift, so will the spatial distribution of natural-ecosystems and agro-ecological zones. Likewise, the distribution patterns of plants, diseases and pests, fish populations and ocean circulation will change, causing potentially significant impacts on food production and livelihoods. This study focuses on MENA, due to current high levels of water stress and a long history of autonomous adaptation knowledge and practices linked to changing patterns of temperature and rainfall. The study sites selected in cooperation with national counterparts reflect important rainfed areas in the main agro-ecological zones defined by the United Nations Food and Agriculture Organization (FAO). The key findings for all the four countries are presented in this report.